Onderhoud: In gesprek met Prof. Cas Wepener - M. Laubscher (Acta Theologica)
Interview: In conversation with Cas Wepener Cas Wepener is professor in Practical Theology at Stellenbosch University since 2019. He teaches liturgy and homiletics. Martin Laubscher interviews Cas Wepener on his life in theology, practical theology and the witness of the church during the pandemic.